Environmental impacts of water pollution at Sungai Jelapang, Ipoh / Muhammad Hafizal Hashim - Hashim, Muhammad Hafizal (Universiti Teknologi Mara, Perak, 2021)
In life, water is a very important natural resource. This is because water is used in daily life, there are five uses of water in daily life, the first of which is for household use such as washing, cooking, drinking, and bathing. Next are general uses, for example uses for cleaning markets and places of recreation, in addition, uses for industry, for example as turbines for the conduction of electricity. It is also used for trade, for example for hotels and restaurants and the latter is for agriculture. In recent years, water -related pollution has increased, thus increasing public concern as well as affecting clean water resources. Among the areas that have been identified as experiencing water pollution is in Jelapang, Ipoh. It is a pollution of the Jelapang river. The cause of water pollution in the Jelapang river is due to waste disposal from industrial areas. As happened in Jelapang, Ipoh, the pollution that occurred was due to the dumping of waste discharged from the rubber glove factory which was discharged into the Jelapang river. As a result, the river is polluted by toxic waste. Therefore, there are three objectives that have been identified to overcome river pollution that occurs in the Jelapang river, Ipoh. The first objective is to identify the source of the polluted river in Jelapang, Ipoh. The second objective is to study the impact on nature and the environment because of the dumping of factory glove waste into rivers. The final objective is to recommend method to control the dumping of waste into the Jelapang river, Ipoh. After identifying the three objectives, then the research method used in collecting data is by distributing questions online through the platform 'Google Form', this method is used because Malaysia was hit by covid 19, so movement has been restricted. Analysis is used by analyzing using Statistical Package for Social Science (SPSS) software. Therefore, the method is suitable to use. The results of the questions that have been distributed found that the pollution that occurred in the Jelapang river, Ipoh has a significant impact on the respondent around the Jelapang area. Among the findings of the main study found that respondents in Jelapang worried about their well -being. Moreover, if the river pollution that occurs is not curbed effectively it has a detrimental effect. Subsequently, the residents in the area suggested holding an awareness campaign related to the pollution of the Jelapang river. The findings of the study from the results of the study led to a proposal to overcome the problems that occur in the Jelapang river. Among the proposals identified is Create a Campaign, the second is to Enforce the Law, the third is the River Environment Management Plan and the last is the Establish a River Management Committee